Introduction to Clinical Clerkships - Susan Kies (Association of American Medical Colleges, 2005)
Abstract The Introduction to Clinical Clerkships is a 2-week course for new third-year students, starting immediately before the core clerkship schedule begins. The course is designed to introduce the students to the clinical program and give each clinical department time to orient them to basic materials and situations before they enter core clerkships. It also reinforces certain clinical issues introduced during the second year. During the planning phase, meetings were held with department heads and clerkship directors to determine the most important elements in each department's clerkship orientation. A larger curriculum committee reviewed areas of the clinical curriculum that overlapped and considered them for placement into the course. Further meetings were held to determine additional skills that would be appropriate for inclusion. During the course, students identify a hospitalized patient from a preassigned service: adult medicine, pediatrics, obstetrics and gynecology, family medicine or surgery. After the student makes contact with the assigned service, the hospital site coordinator assists them in finding a patient. The student then completes a history and physical examination in the same format utilized during their M-2 curriculum. Over the two-week course, students must complete a comprehensive written admission evaluation. During the small-group component, students work with a variety of clinical preceptors to discuss their patients and the information gleaned from the examination of those patients. At the completion of the course, students will have presented, discussed, and documented the various kinds of chart documentation necessary to care for hospitalized patients. Students are evaluated on a pass/fail basis by their clinical preceptors. At the end of the 2 week course, students are individually interviewed regarding their experiences. A follow-up survey is given to students after they complete 3 months of core clerkships and then again after 6 months. Clerkship directors are also surveyed for their comments on student preparation at 3 and 6 months.